2017
DOI: 10.1186/s13012-017-0583-y
|View full text |Cite
|
Sign up to set email alerts
|

Teaching implementation science in a new Master of Science Program in Germany: a survey of stakeholder expectations

Abstract: BackgroundImplementation science in healthcare is an evolving discipline in German-speaking countries. In 2015, the Medical Faculty of the University of Heidelberg, Germany, implemented a two-year full-time Master of Science program Health Services Research and Implementation Science. The curriculum introduces implementation science in the context of a broader program that also covers health services research, healthcare systems, research methods, and generic academic skills. Our aim was to assess the expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 8 publications
4
38
0
3
Order By: Relevance
“…Findings from this evaluation are comparable with other studies evaluating dissemination and implementation training initiatives and identified a number of factors that can be leveraged to enhance future initiatives for implementers [ 22 , 24 , 27 ]. Course facilitators can consider participants’ previous experience with KT (e.g., beginner, intermediate, advanced) [ 46 ] and fit with participants’ previous learning and experience from other fields (e.g., terminology and concepts from physician education, project management, quality improvement, change management, behavior psychology etc.).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Findings from this evaluation are comparable with other studies evaluating dissemination and implementation training initiatives and identified a number of factors that can be leveraged to enhance future initiatives for implementers [ 22 , 24 , 27 ]. Course facilitators can consider participants’ previous experience with KT (e.g., beginner, intermediate, advanced) [ 46 ] and fit with participants’ previous learning and experience from other fields (e.g., terminology and concepts from physician education, project management, quality improvement, change management, behavior psychology etc.).…”
Section: Discussionsupporting
confidence: 74%
“…There is also a gap in the literature describing evaluations of training activities for implementation scientists and practitioners. In response to an editorial in Implementation Science that emphasized the need to rigorously evaluate capacity building initiatives to advance the science and practice of dissemination and implementation [ 26 ], several evaluations of training initiatives were published [ 8 , 22 , 24 , 27 ]. However, to date, many of these studies evaluated training initiatives that targeted researchers with fewer focused on evidence implementation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Articles spanned a 13-year period (2006–2019) with the majority published during or post 2014 ( N = 21) [ 18 , 47 , 57 , 58 , 62 , 88 103 ] and 10 articles published pre 2014 ( N = 10) [ 48 , 49 , 104 – 111 ]. Publications originated from 8 countries: the USA ( N = 21) [ 18 , 48 , 57 , 58 , 62 , 88 – 90 , 92 96 , 98 101 , 103 , 104 , 108 , 109 ], Canada ( N = 3) [ 106 , 107 , 110 ], Australia ( N = 2) [ 49 , 91 ], the UK ( N = 1) [ 105 ], Sweden ( N = 1) [ 47 ], Kenya ( N = 1) [ 97 ], Germany ( N = 1) [ 102 ] and Saudi Arabi ( N = 1) [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 41 D&I CBIs identified, a range of ‘types’ of training (as defined by the authors of each of the included articles) were reported including training Institutes ( N = 4) [ 18 a , 48 , 57 , 92 , 103 , 106 , 107 , 109 , 110 c ] or courses that were part of training programmes ( N = 2) [ 18 b , 98 , 100 ] or training initiatives ( N = 1) [ 99 ]; workshops ( N = 4) [ 49 , 93 , 95 , 111 ], seminars ( N = 3) [ 90 a , 110 a,b ], clerkships ( N = 1) [ 88 ], mentorship programmes ( N = 1) [ 90 b ], graduate certificates ( N = 1) [ 89 ], webinars ( N = 1) [ 90 c ], fellowship programmes ( N = 1) [ 97 ], master’s programmes ( N = 1) [ 102 ] or modules that have been integrated in master’s programmes—including clinical research ( N = 1) [ 104 a ] primary health care ( N = 1) [ 105 ] and public health ( N = 1) [ 62 ]; or PhD programmes ( N = 1) [ 94 ] or modules that are integrated as part of a Doctors of Nursing programme ( N = 2) [ 101 , 108 ]. The 15 remaining CBIs were termed by the authors as ‘courses’ relating (in part or in full) to D&I science [ 18 c,d , 47 , 58 , 91 , 96 , 104 b,c , 110 d-k ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors state that an in-depth analysis of the quality of programs would aid in the planning of other programs in the area. Assessment of a master-level implementation science course in Germany found that stakeholders’ expectations primarily concerned acquiring knowledge about implementation strategies and knowledge of barriers and enablers, suggesting that implementation practice was considered more important than implementation science from a stakeholder perspective [ 5 ]. It is worth mentioning that education regarding implementation research in health care is provided also by the World Health Organization [ 6 ].…”
Section: Introductionmentioning
confidence: 99%